THE REPRESENTATION OF THE CULTURAL IDENTITY OF THE KOMERING ETHNIC GROUP IN THE SAMBUT SEBIDUK SEHALUAN DANCE IN EAST OGAN KOMERING ULU REGENCY - Riska Amanda; Rosta Minawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Sambut Sebiduk Sehaluan Dance is a welcoming dance originating from East Ogan Komering Ulu Regency, South Sumatra, officially created in 2007 as a representation of the cultural identity of the Komering community. Historically, Komering culture does not stem from the Malay tradition but developed under the geographical and cultural influence of the neighboring Lampung region, while Malay elements emerged later through historical interactions, transmigration processes, and regional cultural policies following administrative division. This study aims to analyze the representation of Komering cultural identity in the Sambut Sebiduk Sehaluan Dance by examining the meaning of the dance’s name, movement structure and quality, its relationship with the Komering River, costumes, properties, and the religious values underlying its formation. The research employs a qualitative approach using dance ethnography, with data collected through performance observation, in-depth interviews with the founder of the art studio, and documentation and historical studies. The findings show that the concept of Sebiduk Sehaluan, meaning “one boat, one shared goal,” reflects the Komering community’s life philosophy centered on togetherness, harmony, and ecological relationships with the Komering River. The dance movements are dominated by flowing qualities inspired by the dynamics of the river and the community’s daily activities. Strong Islamic values are reflected in the dancers’ bodily ethics, spatial limitations of movement, and the ceremonial presentation of the tepak as a symbol of respect and openness. This dance represents Komering cultural identity rooted in river cosmology, Islamic religiosity, and the region’s historical dynamics.